Polyvinyl Butyral (PVB) Nanofiber/Nanoparticle-Covered Yarns for Antibacterial Textile Surfaces - Yalcinkaya, Fatma; Komarek, Michal (International journal of molecular sciences, 2019)
In this study, nanoparticle-incorporated nanofiber-covered yarns were prepared using a custom-made needle-free electrospinning system. The ultimate goal of this work was to prepare functional nanofibrous surfaces with antibacterial properties and realize high-speed production. As antibacterial agents, we used various amounts of copper oxide (CuO) and vanadium (V) oxide (V2O5) nanoparticles (NPs). Three yarn preparation speeds (100 m/min, 150 m/min, and 200 m/min) were used for the nanofiber-covered yarn. The results indicate a relationship between the yarn speed, quantity of NPs, and antibacterial efficiency of the material. We found a higher yarn speed to be associated with a lower reduction in bacteria. NP-loaded nanofiber yarns were proven to have excellent antibacterial properties against Gram-negative Escherichia coli (E. coli). CuO exhibited a greater inhibition and bactericidal effect against E. coli than V2O5. In brief, the studied samples are good candidates for use in antibacterial textile surface applications, such as wastewater filtration. As greater attention is being drawn to this field, this work provides new insights regarding the antibacterial textile surfaces of nanofiber-covered yarns.
Keywords: copper; Polyvinyls; antibacterial; Nanofibers; antibakteriální látky; Vanadium; electrospinning; PVB; měď; Copper; nanovlákna; vanadium; vanad; Anti-Bacterial Agents; polyvinyly; nanoyarn